2018
DOI: 10.6026/97320630014540
|View full text |Cite
|
Sign up to set email alerts
|

A review on Respiratory allergy caused by insects

Abstract: Hypersensitivity or allergy encompasses a wide range of immunological reactions that generally have adverse consequences involving one or many organ systems of the body. Allergens are usually glycoprotein or chemically complex low molecular weight substances. The common allergens include pollen, fungal spores, house dust mite and house dust, animal danders, drugs, foods, insect emanations, and detritus, etc. Information on the role of insects in respiratory allergy is increasing in the literature. There are ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 102 publications
(95 reference statements)
0
16
0
1
Order By: Relevance
“…Multiple insects and arachnids have been shown to cause allergies that are unrelated to stinging or any form of “active” toxicity (i.e. venom) [ 56 ]. Likewise, cutaneous, ocular, and respiratory exposure to venoms from spitting cobra ( Hemachatus hemachatus ) and South American Crotalinae vipers ( Bothrops asper , B. atrox , B. jararaca , B. xanthograma , Crotalus durissus terrificus , Lachesis muta ) originate allergenic responses [ 57 - 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple insects and arachnids have been shown to cause allergies that are unrelated to stinging or any form of “active” toxicity (i.e. venom) [ 56 ]. Likewise, cutaneous, ocular, and respiratory exposure to venoms from spitting cobra ( Hemachatus hemachatus ) and South American Crotalinae vipers ( Bothrops asper , B. atrox , B. jararaca , B. xanthograma , Crotalus durissus terrificus , Lachesis muta ) originate allergenic responses [ 57 - 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A clinico-immunological study concluded that mosquito debris could be a potent inhalant allergen in indoor air (Kausar et al 2007 ). Dermatophagoides pteronyssius (Der p I & Der p II) and Dermatophagoides farinae (Der f I) are major species of mites that produce allergens (Kausar 2018 ). Bakery, poultry, granary and sugar industry are major sources for allergens in the indoor environment.…”
Section: Components Of Biological Contaminantsmentioning
confidence: 99%
“…1 All material form insects namely wings, scales, saliva, dried feces and venom can cause allergic diseases. 2 For standard treatment of allergy, medications for allergic patients are antihistamines and corticosteroids. 3 Additionally, allergen vaccination is a standard immunotherapy for allergic disease.…”
Section: Introductionmentioning
confidence: 99%